دراسة تـأثير عملية تصنيع اللواقط الشمسية ذات الأنابيب المفرغة على أدائها الحراري - لبان نديمة (Latakia University Journal -Engineering Sciences Series, 2018)
The standard of living of any country depends on the energy security of its citizens, and when the Developing Countries seeks to Raising the level of civilization and their Population growth they will need more energy, this resulted to the trend towards renewable energies that include solar energy, which is largely used in the domain of water heating by the mean of evacuated tubes technique, that′s why it is an necessity doing an statistical study of all types of solar collectors, that uses evacuated tubes in the Syrian market, and compare the characteristics of each one of those types by listing those characteristics for all mentioned types into comparison tables then making the choice of two types, those chosen two types have similar characteristics in the tank volume and must have the same number of evacuated tubes, with the difference between those two types in the fabrication materials, and one of the two types have more accurately indicated and listed characteristics than the other, then calculating of the solar radiation was done and its rate was determined using Achry method, the study of the two types of water heater was done taking in count different weather states in all seasons and with respect to time, in this study the heated water temperature change with respect to time was determined and listed into tables and graphical representations, then an comparison was done on those results and calculation of the output ratio also for the two chosen types of water heaters by the mea determining of the solar collector constants for each type and showing that graphically and doing an general evaluation of the solar water heaters that uses evacuated tubes, in this way this study is an essential reference to be used by consumers and investigators how have the desire to buy an solar collector suitable for their daily needs of heated water by volume and quality that have the least possible cost. Demonstrating that effect the Manufacturing process of evacuated tubes solar captors on their thermal performance. يتوقف مستوى المعيشة في أي بلد على تأمين الطاقة بمختلف أشكالها للمواطنين، وعندما تسعى البلاد النامية إلى رفع مستواها الحضاري واستيعاب نموها السكاني، فإنها ستحتاج إلى المزيد من الطاقة، فكان الاتجاه نحو الطاقات المتجددة ومنها الطاقة الشمسية، حيث تستخدم بشكل كبير في مجال تسخين المياه وفق تقنية الأنابيب المفرغة، لذلك كان لابد من دراسة احصائية لكل نماذج اللواقط الشمسية ذات الأنابيب المفرغة في السوق السورية ومقارنة المواصفات لكل منها من خلال ادراجها ضمن جداول مقارنة. ثم اختيار نوعين لهما مواصفات متماثلة في سعة الخزان وعدد الأنابيب المفرغة وكان الاختلاف في مواد التصنيع وأن أحد هذين النوعين يقدم ويعرض مواصفات أكثر دقة من الأخر، ثم حسبت شدة الاشعاع الشمسي وحددت معدلاته وفق طريقة أشري، وتم اجراء الدراسة لكل من السخانين مع الأخذ بعين الاعتبار الظروف المناخية على مدار فصول السنة، حيث تم تحديد تغير حرارة الماء الساخن لكل منهما تتابعية مع الزمن وعرضت ضمن جداول ومنحنيات بيانية، ومن ثم اجراء مقارنة لتلك النتائج وحساب المردود لكلا السخانين من خلال تحديد ثوابت اللاقط الشمسي لكل منهما وتمثيل ذلك بيانياﹰ، وتقييم عام اللواقط الشمسية المفرغة، وبذلك تكون هذه الدراسة مرجعاﹰأساسياﹰ للمستهلكين والمستثمرين الراغبين بشراء السخان الشمسي المناسب لاحتياجاتهم اليومية من الماء الساخن حجماﹰ ونوعاﹰ بأقل كلفة ممكنة، موضحين يذلك أثر عملية تصنيع اللواقط الشمسية ذات الأنابيب المفرغة على أدائها الحراري.